2022
DOI: 10.1063/5.0122109
|View full text |Cite
|
Sign up to set email alerts
|

Frenkel exciton photodynamics of self-assembled monolayers of azobiphenyls

Abstract: We performed computational simulations of the photodynamics of a self assembled monolayer (SAM) of an azobenzene derivative (azobiphenyl, ABPT) on a gold surface. An excitonic approach was adopted in a semiempirical framework, which allowed to consider explicitly the electronic degrees of freedom of 12 azobenzene chromophores. The surface hopping scheme was used for the nonadiabatic molecular dynamics simulations. According to our results for an all trans-ABPT SAM, the excitation energy transfer between differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
31
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(36 citation statements)
references
References 20 publications
5
31
0
Order By: Relevance
“…Notably, after transition to the nπ * manifold, the exciton is strongly localized (F 22 = 1, F H = 1, IPR = 1; FTDM and IPR curves are less noisy than for the ππ * manifold) and it remains at a single fragment (X = 2 for the shown trajectory) without being transferred. This is in agreement with the recent conclusion of Sangiogo Gil et al 46 Importantly, the absence of the exciton transfer in the nπ * manifold is observed for almost all trajectories with an exception of two trajectories for tetramer 3.5 Å and two trajectories for SAM 3.5 Å. And for these exceptional trajectories, only a single transfer event takes place per trajectory.…”
Section: Lphivsupporting
confidence: 92%
See 4 more Smart Citations
“…Notably, after transition to the nπ * manifold, the exciton is strongly localized (F 22 = 1, F H = 1, IPR = 1; FTDM and IPR curves are less noisy than for the ππ * manifold) and it remains at a single fragment (X = 2 for the shown trajectory) without being transferred. This is in agreement with the recent conclusion of Sangiogo Gil et al 46 Importantly, the absence of the exciton transfer in the nπ * manifold is observed for almost all trajectories with an exception of two trajectories for tetramer 3.5 Å and two trajectories for SAM 3.5 Å. And for these exceptional trajectories, only a single transfer event takes place per trajectory.…”
Section: Lphivsupporting
confidence: 92%
“…In our present work, we also come to a similar conclusion, and in what follows we will compare our results to the results of Ref. 46 where applicable.…”
Section: Introductionsupporting
confidence: 86%
See 3 more Smart Citations